Hepatic Haemangioma: A Diagnostic Dilemma with an Easy Solution - Haider Bin Khalid; Aamna Hassan; Sana Munir Gill (Journal of the Pakistan Medical Association, 2023)
Hepatic Haemangioma is the most common benign liver tumour. There are two types of haemangiomas: capillary haemangioma and cavernous haemangiomas. The term “giant haemangioma” is reserved for lesions larger than 5 cm. Given the abundance of vascular structures around the liver, SPECT/CT hybrid imaging with 99mTc labelled Red Blood Cells (RBCs) constitutes an excellent modality for localization and characterization of hepatic haemangiomas. Keywords: Hepatic haemangioma; SPECT/CT; 99mTc labelled red blood cell (RBC)